Evaluation Self Confidence of Hospitality Class Students at Vocational High Schools - Izzah Mufliha; Geraldine Anne Tan; Manika Wisessathorn (Indonesian Journal of Education Research (IJoER), 2022)
Purpose of the study: This research aims to describe in depth the level of self-confidence of class XII students majoring in hospitality at Public vocational secondary schools 4 Sarolangun, providing important insights for educational development and a better understanding of the factors that influence students' self-confidence. Methodology: The research method used in this research is descriptive quantitative. The population used in this research were Class XII students majoring in Hospitality at Public vocational secondary schools 4 Sarolangun. The sampling technique used in this research was purposive sampling. The data collection instrument used was a questionnaire. The data collection instrument used was a questionnaire. Main Findings: Based on the results showing the level of self-confidence of class XII students majoring in Hospitality, it was found that the average self-confidence score was in the good category. Students have good abilities in facing and resolving challenges faced in the context of vocational education in the hospitality sector. These results indicate that the majority of class Novelty/Originality of this study: The novelty of this research is the special focus on class This opens up new opportunities for a deeper understanding of the dynamics of self-confidence in the context of vocational education.